A country scale assessment of the heat hazard-risk in urban areas. (1st February 2023) - Cheval, Sorin; Dumitrescu, Alexandru; Amihăesei, Vlad; Irașoc, Adrian; Paraschiv, Monica-Gabriela; Ghent, Darren
Abstract: The connexion between the regional climate and urban environment produces local changes in most climate features and exacerbates the magnitude and frequency of the extreme events. Heat hazards are particularly related to urban climate and global warming will amplify the associated risks in vulnerable areas and their environmental impacts. This paper presents the results of interdisciplinary environmental research aiming to provide a country scale perspective of the heat hazard-risk (HHR). We have used a risk matrix approach combining elements of thermal hazard, derived from land surface temperature (LST), and vulnerability metrics, derived from population density and urban fabric. The study informs about the overall factors that control the HHR across 77 cities in Romania, such as the environmental and climate settings, the city size and structure. The results show that the urban HHR is higher during the daytime, in warmer climates and in densely populated cities. The use of the methodology at a country scale is innovative, and demonstrates clear potential for applications in other regions, mainly for national strategies and plans aiming to mitigate the urban HHR within the climate change context. Highlights: Urban heat hazard-risk is analysed at a country scale using a risk matrix approach. MODIS Land Surface Temperature data define the heat hazard. Local Climate Zones and population density define the vulnerability. The geographical and climate settings, and city features trigger heat hazard-risk. The results enable the national authorities to reduce the heat hazard-risk.